DESIGN AND BUILD AN IMMIGRATION STAY PERMIT E-ALERT APPLICATION AT THE ANDROID-BASED NON-TPI SERANG CLASS I IMMIGRATION OFFICE - W Wilonotomo; Gunawan Ari Nursanto; Nico Harmono Putra (Polteknik Imigrasi, 2021)
The revolution of industry 4.0 encourage people to travel to another countries with different paths. Foreigners who entered to Indonesia must have a valid residence permit. The granting of a residence permit is given by the Directorate General of Immigration through the Immigration Office and sent via email so that many foreigners not careful about the validity period of their residence permit. To provide excellent immigration services and supervision, the Directorate General ofImmigration always makes innovations that can make every job easier. In addition, by designing an Android-based immigration residence permit e-alert application, it can prevent foreigners from committing immigration violations in the form of overstay. In this study the method used is the waterfall system development method where all activities are carried out sequentially to obtain optimal results. The system development application used is Android Studio and Firebase. The method is divided into 5 (five) parts, requirements analysis, design, implementation, testing, and maintenance. The results of this study are in the form of a prototype that can be run using an Android-based emulator and can be used as an innovation reference at First Class of Serang Immigration Office.